Colemanite In Steel Production - Levent Özmen (The Minerals, Metals and Materials Society, 2006)
Colemanite is a mineral containing varying amount of boron that is found in abundance in Turkey. It has a good possibility to be used as a flux in iron and steel industry. In this study a review of the use of colemanite, as a flux agent in steel production has been carried out and various related aspects such as its influence in metal-slag reactions, solubility of lime and magnesia in the slag are discussed along its performance in several points of views including its technical and environmental usage characteristics. Positive and negative factors of using this material as a flux are also underlined.